Forced migration and attitudes towards domestic violence: Evidence from Turkey - Selim Gulesci (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
I explore the long-term effects of internal displacement caused by the Kurdish-Turkish conflict on women's attitudes towards domestic violence. Using the Turkish Demographic and Health Survey, I show that forced migrants are more likely to view domestic violence as acceptable. As suggestive evidence, I use data from applicants to a women's shelter and show that forced migrant women endure violence for longer and of greater intensity before deciding to seek assistance. I discuss possible mechanisms through which forced migration may affect migrants' attitudes towards domestic violence.
Keywords: D13; D74; J12; J61; 330; forced migration; domestic violence; long-run effects